2021
DOI: 10.1002/mde.3321
|View full text |Cite
|
Sign up to set email alerts
|

Firm internationalization and long‐term impact of the Covid‐19 pandemic

Abstract: We infer market expectations regarding the relationship between firm internationalization and the long‐term impact of the Covid‐19 pandemic by using a novel approach to decompose global stock prices into their short‐ and long‐term value components. In general, firms with a greater proportion of foreign assets show greater losses in the long‐term value component, suggesting investor expectations of higher supply‐chain restructuring costs for such firms. Also, investors appear to have priced in the likely perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…They believed this will have consequences for everyone as international mobility will decrease. This is in line with predictions from the literature (Caligiuri, 2020; Nagarajan and Sharma, 2021), and it is a significant consideration for the theory and practice of global mobility.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…They believed this will have consequences for everyone as international mobility will decrease. This is in line with predictions from the literature (Caligiuri, 2020; Nagarajan and Sharma, 2021), and it is a significant consideration for the theory and practice of global mobility.…”
Section: Discussionsupporting
confidence: 89%
“…Radical change in work setting due to COVID-19 restrictions In this highly globalised situation within the given gender regime, a highly contagious disease appeared, and most countries introduced a curfew and lockdown with international travel restricted to a minimum (Caligiuri et al, 2020;Moore and Collins, 2021;Nagarajan and Sharma, 2021). Consequently, many people began to work from their homes using online platforms, and unnecessary travel and social contacts were reduced and international travel all but disappeared (Jackson, 2020).…”
Section: Jgm 102mentioning
confidence: 99%
“…This is related to the uncertainty that the COVID-19 outbreak has brought, creating a new situation where the shortterm consequences are somehow known, but in the long term, uncertainty is evident. Nagarajan and Sharma (2021) show that COVID-19 has a crossindustry and cross-economic impact, and firms with a higher proportion of foreign assets may experience more significant long-term losses.…”
Section: Financial Determinants Of Sme Activity In Developing Countriesmentioning
confidence: 99%
“…Nagarajan and Sharma [2] studied the changes in global equity valuations after the outbreak of the COVID-19 pandemic to infer market's expectations regarding the possible long-term impact of the pandemic on global supply chains. Amiti et al [3] found that the costs of tariffs imposed in the United States were mainly borne by American consumers.…”
Section: Literature Reviewmentioning
confidence: 99%